ELISA versus Nested PCR for Detection of Hepatitis B Co-infection in HIV-infected People in Bandung Indonesia - Naully, Patricia Gita (KnE Life Sciences, 2021)
The number of Human Immunodeficiency Virus infected patients in Bandung is increasing. HIV patients are often suffering from Hepatitis B Virusco-infection. The co-infection status must be detected using the accurate method. This study aims to compare the accuracy of Enzyme-Linked Immunosorbent Assay and nested Polymerase Chain Reaction in detecting HIV-HBV co-infection in Bandung. The research method used is experimental. The sample used in this study was 50 people. All samples had met the inclusion criteria. The presence of hepatitis B surface antigen in the serum was detected using a qualitative ELISA Wantai kit, while sHBsAg gene in the whole blood was amplified using 2 pairs of the specific primary. The results obtained from both methods were analyzed to determine sensitivity, specificity, and accuracy values. The result of Hepatitis B detection using ELISA method showed that 15 samples (30%) were positive, 1 sample (2%) was a false positive, and 3 samples (6%) were the false negative. Moreover, the nested PCR method showed that 18 samples (36%) were positive without false positive or false negative result. These results showed that ELISA has a sensitivity value of 83.33%, specificity of 96.87%, and the accuracy of 92%, while Nested PCR has a value of 100% for all three parameters. Therefore, it can be concluded that the Nested PCR method was more accurate than ELISA to detect Hepatitis B co-infection in HIV patients in Bandung.The Nested PCR can be recommended for detecting the other co-infection cases. Keywords: accuracy, HBsAg, co-infection, sensitivity, specificity